Shielding design and calculation of a treatment room for a 15-MV versa HD LINAC at BMU, Dhaka, Bangladesh - Uddin, M. Jamal; Rana, Muhammad Masud; Harun-Or-Roshid; Dilshad, Taskin (International Journal of Research in Medical Sciences, 2025)
Background: Effective shielding design is essential for ensuring radiation safety for both patients and healthcare staff in medical radiation therapy facilities, particularly with high-energy LINACs. This study investigates the shielding design and calculation for a 15-MV versa HD LINAC treatment room at Bangladesh Medical University (BMU), focusing on primary and secondary radiation barriers. Methods: Shielding design and calculation were performed using empirical equations based on NCRP report no. 151 (2005). Maximum photon energy (15 MV) was considered for barrier design. Calculations for primary and secondary barrier thicknesses were performed using workload, use factor, and occupancy factor, with ordinary concrete (2.35 g/cm³) as the material. Radiation levels were measured at various gantry positions (0°, 90°, and 270°) with calibrated radiation detectors. Results: The primary barrier thicknesses were calculated as 2.75 m for east and west sides, and 2.58 m for the roof. Secondary barrier thicknesses for the north, south, and roof sides were 1.02 m, 1.14 m, and 1.18 m, respectively. Radiation measurements at different gantry angles showed a maximum photon dose rate of 2.15 μSv/hr at the main entrance door, with values consistently below 10 μSv/hr at all locations. The standard deviation of dose rates ranged from 0.03 to 0.15 μSv/hr. Statistical analysis showed a p=0.04, indicating significant differences between radiation exposure at different gantry positions. The coefficient of variation (CV) was calculated as 0.23%, confirming low variability in the shielding performance across measurements. Conclusions: The shielding design effectively meets safety standards, with radiation levels well below permissible limits, ensuring the safety of both hospital staff and patients.